Effectiveness of an educational program in cardiopulmonary resuscitation concerning knowledge of nurses in Cyprus - Gregoriou, P.; Theodorou, Mamas; Bilali, Angeliki; Rousou, Elena; Charitou, Andreas; Galanis, Petros (My University, 2015)
INTRODUCTION: Nurses’ education in Cardiopulmonary Resuscitation (CPR) is essential, but there are considerable deficiencies. AIM: To estimate the knowledge of nurses before a specialized in hospital educational program in CPR, and to investigate the effectiveness of this program immediately after its completeness and six months later. METHODS: Study was conducted in all wards of the Limassol General Hospital and included 294 nurses. Data collection was done using a specially designed questionnaire based on the international literature and guidelines of the European Resuscitation Council 2010. Total knowledge score was between 0-9 with higher values indicate higher knowledge. RESULTS: Mean knowledge score before the educational program was 4.3, while after the program increased considerably to 8.6, reaching the maximum value of 9. Mean knowledge score six months after the educational program decreased to 6.4, but still remained higher than the knowledge score before the program. We found a statistically significant increase in knowledge score immediately after the end of the program and also six months later (p<0.001 in both cases). Decreased years of work experience was associated with increased knowledge score (p=0.047). CONCLUSIONS: Continuous education of nurses in CPR is essential in order to increase and maintain the knowledge. In that case, nurses could apply CPR in an appropriate and effective way every time there is a need for that.
Keywords: Cardiopulmonary resuscitation; Cyprus; Educational program; Effectiveness; Knowledge; Nurses